On the importance of the sowing time of crucifers in preventing the damage caused by cabbage maggots (Hylemyia spp), on the basis of tests made on big-leafed turnip - Anna-Liisa Varis (Scientific Agricultural Society of Finland, 1958)
In investigating the importance of the sowing time of crucifers in preventing the damage caused by the cabbage maggots (Hylemyia spp) the big-leafed turnip (Brassica rapa L. v. rapifera Metzg.) was used as a test plant. In regard to the abundance and severity of the damage differences occured in the test plants sown at different times. In South-Finland, however, the order varied in different years so that damage caused by the cabbage maggots can generally not be avoided by an arrangement of the sowing time. In North-Finland the early sowings were generally somewhat more severely damaged than the later ones. The postponement of the sowing time, however, had a detrimental effect on the yields and despite the fairly severe damage the best yields were obtained from the early sowings.